Cheating in exams and the attribution of the failure and success among university students - Kemiha, Ismahane; Djenidi, Abla (Journal of Human Sciences, 2022)
This study aimed to find out the category of factors that university students attribute to their academic failure and an attempt to resort to the process of cheating in exams. For this reason, we applied a semi-directed interview to an intentional sample consisting of 15 male and female students who tried or actually practiced cheating during their university course, and who are pursuing their studies in the first year of a master’s degree at the Faculty of Psychology and Education Sciences at the University of Constantine 2. By using the Berlson method to analyze the content of the responses of the members of the research sample, we reached the following results: A large percentage of students attributed their failure to internal factors that are insufficient efforts, lack of achievement motivation, inability to understand because of the lacking of the processes of attention and concentration in lessons, which lead to forgetting information. And all of this may have a direct contribution in pushing them to exam’s cheating for maintaining a high level of self-esteem.